PENGARUH KUALITAS PRODUK, INOVASI PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN MINAT BELI ULANG DI IKEA - Arizal, Syahrezi (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
This study aims to analyze the influence of product quality, product innovation, and promotion on repurchase decision on IKEA. The sample used is 180 respondent, calculated based on maximum likelyhood estimation formula. The sampling method using nonprobalibity sampling, with sampling type is convenience sampling. The method of data collection using google form method. The data analysis method using Partial Least Square 3.0. The results of this study indicate that product quality has a positive and significant effect on repurchase decision, Product innovation has a positive and significant effect on repurchase decision, And promotion has a positive and significant effect on repurchase decision on IKEA.